Sulfuryl fluoride as a methyl bromide alternative for fumigation of Necrobia rufipes (Coleoptera: Cleridae) and Tyrophagus putrescentiae (Sarcoptiformes: Acaridae), major pests of animal-based stored products. (March 2021) - Hasan, Md Mahbub; Aikins, Michael J.; Schilling, M. Wes; Phillips, Thomas W.
Abstract: Sulfuryl fluoride (SF) has been registered in many countries for stored product applications as an alternative to other fumigants, especially methyl bromide (MB). Research was conducted to establish SF fumigation protocols for the mortality of pests infesting post-harvest durable commodities. The efficacy of SF against two major arthropod pests of southern dry-cured hams, the red-legged ham beetle, Necrobia rufipes, and the ham mite, Tyrophagus putrescentiae, was investigated. SF caused significant mortality in ham beetles but not for ham mites when treated for 48 h at 23 °C. Eggs of N. rufipes were more tolerant to SF than other stages fumigated. In addition, early aged (1–2 d old) eggs of N. rufipes were more susceptible to SF than late-aged (4–5 d old) eggs. Furthermore, SF fumigation led to 100% control of larvae, pupae and adults of N. rufipes by 8 g/m 3 while the eggs required 20.88–24.72 g/m 3 to prevent 100% hatch. However, T. putrescentiae showed high tolerance to SF as it survived concentration-time products in excess of the standard label limit 1500 g h/m 3 . SF studies also revealed that the eggs of T. putrescentiae were several fold more tolerant than that of the mobile stage, the nymphs and adults. SF trials under pilot-scale commercial conditions were also carried out that further supported the efficacy of SF for red-legged ham beetles but not for the ham mite. SF may not be suitable for managing ham mites based on work to date, but future work could investigate longer exposure times at higher temperatures. Highlights: Methyl bromide (MB) fumigant was used routinely for control of pests on dry-cured hams. MB was banned for use on hams; sulfuryl fluoride (SF) is an alternative allowed for hams. Lab experiments tested SF against the red-legged ham beetles and ham mites. SF killed all life stages of the beetle, but not mites within the legal concentration. Alternative fumigants of other control methods are needed for ham mite infestations.